SIMULTANEOUS DISC HERNIATION IN PATIENTS WITH MULTIPLE SCLEROSIS - Kalina V. Drenska; Ara G. Kaprelyan; Alexandra J. Tzoukeva; Radoslav Georgiev; Ilia T. Todorov (Peytchinski Publishing, 2013)
Background: Multiple sclerosis (MS) is a chronic autoimmune, inflammatory demyelinating disease of the central nervous system. Commonly, MS patients present with accompanying degenerative vertebral disc diseases. Simultaneous disc herniations situated in the cervical or lumbosacral spine can mimic the clinical symptoms of MS and worsen patients' quality of life.Objective: to investigate the incidence rate and clinical impact of accompanying disc herniations in patients with MS.Material and methods: Our study covered 330 patients (220 females and 110 males, mean age 40.5±12.4 years) with clinically definite MS, according to McDonald's criteria. Comprehensive neurological examinations, EDSS (Expanded Disability Status Scale) assessments, and MRI neuroimaging were carried out. Statistical data processing was performed by using the method of variation analysis.Results: Relapsing-remitting MS (RRMS) was diagnosed in 280 patients while 50 patients presented with secondary progressive MS (SPMS). Disc herniation was found in 64 (19.4%) of our patients. Cervical disc pathology was detected in 38 patients (11.5% of the cases) and lumbosacral - in 26 (7.9% of the cases). EDSS scores ranged from 2.5 to 5.5. EDSS evaluation showed statistically significantly worse scores in MS patients with disc herniation comorbidity (p<0, 05).Conclusion: Our own data confirm the assumption that MS patients often present with accompanying degenerative disc pathology. We suggest that comorbidity of disc herniation and MS exert an additional unfavorable effect on patient's disability and individual quality of life.